2011
DOI: 10.1177/1934578x1100600529
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Commercially Available Herbal Products

Abstract: Herbal products are believed to be safe as they are naturally occurring, however, this is a misconception. Currently, there are many herbal products which are not manufactured under the Good Manufacturing Practice (GMP) guidelines and hence the quality of the product is not controlled. Quality can be assessed by evaluation of data on levels of either active constituent(s) or chemical markers indicative of origin of plant material. Assessment of published data on levels of quality of herbal medicinal products r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
6
0
2
Order By: Relevance
“…In effect, although specifications for purported active ingredients may be provided by bodies such as the US Pharmacopeia, compliance to these specifications is voluntary. Therefore, products on the marketplace often display a wide range of constituent concentrations that often differ significantly from label claims (Draves and Walker 2003; Edwards and Draper 2003; Fransen et al 2010; Harkey et al 2001; Ruparel and Lockwood 2011). This lack of consistency in content found in products available on the marketplace presents a considerable challenge in test article selection for NTP studies with herbal products.…”
Section: Current Mixtures Research At Niehsmentioning
confidence: 99%
“…In effect, although specifications for purported active ingredients may be provided by bodies such as the US Pharmacopeia, compliance to these specifications is voluntary. Therefore, products on the marketplace often display a wide range of constituent concentrations that often differ significantly from label claims (Draves and Walker 2003; Edwards and Draper 2003; Fransen et al 2010; Harkey et al 2001; Ruparel and Lockwood 2011). This lack of consistency in content found in products available on the marketplace presents a considerable challenge in test article selection for NTP studies with herbal products.…”
Section: Current Mixtures Research At Niehsmentioning
confidence: 99%
“…The current perception of plant products, that "there'll be no problem because it's natural", may well have influenced the preference for their use. 36 Another frequently chosen plant product is black cumin oil. This plant has great religious significance in Muslim societies, and Turkey is a predominantly Muslim societ.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the numerous papers alleging 'unrecognized' safety for herbals [2,8,12,[17][18][19]20] should be viewed in the context of type and regulation of the products.…”
Section: Regulation Of Herbal Medicinal Products In the Eu With Regarmentioning
confidence: 99%
“…While some patients ask for herbal preparations as an alternative or complement (co-use, administration) to chemically defined substances, other patients use them as they are easy to access, especially in developing countries [3,[5][6][7]. Herbal medicines are repeatedly stated to be natu-1 3 ral and therefore safe when compared to chemical medicines [1, [8][9][10][11][12][13][14][15]. It is common knowledge that only a minor percentage of adverse drug reactions (ADR) to medicinal products is reported to companies or authorities with estimated less than 10 % for prescription (chemical) medicines [4,9].…”
Section: Introductionmentioning
confidence: 99%